Efficacy of LVIS vs. Enterprise Stent for Endovascular Treatment of Medium-Sized Intracranial Aneurysms: A Hemodynamic Comparison Study - Li, Wenqiang; Wang, Yang; Zhang, Yisen; Wang, Kun; Zhang, Ying; Tian, Zhongbin; Yang, Xinjian; Liu, Jian (Frontiers in Neurology, 2019)
Background: We conducted a computational fluid dynamics (CFD) study and compared the treatment of medium-sized intracranial aneurysms with LVIS and Enterprise stent-assisted coil embolization (SACE) to determine the effects of hemodynamic changes caused by different stent and coil packing densities (PDs) in endovascular treatment. Methods: We enrolled 87 consecutive patients, with 87 medium-sized intracranial aneurysms (≥7, ≤ 12 mm), who underwent LVIS or Enterprise SACE. Aneurysms treated with LVIS SACE were allocated to the LVIS group, and the remainder were allocated to the Enterprise group. CFD were performed to assess hemodynamic alterations between before treatment, after stent deployment, and after SACE. Results: One aneurysm recanalized in the LVIS group (n = 42), and five recanalized in the Enterprise group (n = 45) (recanalization rate: 2.4 vs. 11.1%, respectively; P = 0.108). Higher complete obliteration rate (P = 0.069) was found in the LVIS group. Velocity at the neck plane showed a greater reduction ratio than velocity and WSS of the aneurysm in both groups after stent deployment, while velocity and WSS of the aneurysm showed a greater reduction ratio after coil placement. Further, there was a greater reduction in velocity at the neck plane (59.52 vs. 39.81%), aneurysmal velocity (88.46 vs. 69.45%), and wall shear stress (WSS) (85.45 vs. 69.49%) on the aneurysm in the LVIS group (P < 0.001 for all). Specifically, the reduction ratio of velocity at the neck plane showed significant difference between the groups in the multivariate analysis (P = 0.013). Conclusions : LVIS SACE showed a lower recanalization for endovascular treatment of medium-sized intracranial aneurysms, and the greater hemodynamic alterations might be the key factors.